Emergent Strategy and Grand Strategy : How American Presidents Succeed in Foreign Policy - Popescu, Ionut C. (Book collections on Project MUSE., 2017)
"Is following a coherent grand strategy the key to achieving successful outcomes in American foreign policy? For many experts in academia and Washington, the answer is yes. Policymakers usually face criticism when they take incremental actions based on short-term considerations. But could such actions actually converge into a successful emergent strategy over time? Ionut Popescu conclusively shows that in some cases an emergent learning model leads to better overall strategic performance than a long-term strategic plan or framework. Popescu argues that it is time to rethink the origins of some of the most important successes and failures of America's tenure as a global superpower after World War II. Presenting empirical data culled from archival research and interviews with higher-ups, Popescu covers eight US presidential administrations, ranging from Truman to Obama, to demonstrate that senior policymakers should be skeptical of the idea that formulating and implementing a long-term grand strategy is the road to a successful foreign policy legacy. Instead, the book asserts, leaders should prioritize learning from the almost unavoidable mistakes they will make early in their careers and adapting their plans to unanticipated events and changes in the international environment. Emergent Strategy and Grand Strategy thus offers both scholars and practitioners of foreign policy an original theoretical framework to explain strategic success"--